(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Wildfire causes a severe impact on the ecosystem may. It has occurred naturally or manmade. Nowadays, the construction of buildings takes place everywhere, even in the forest surrounding region also. So the surrounding people have to face a lot of troubles through these forest fires. Sometimes it leads to serious health issues as a natural wildfire cannot be avoided but can be timely detected and dealt with by effectively using the available technologies. The Internet of things comes to mind as a first choice due to its special features. Our project sensor is used to detect the fire by Node MCU information is updated continuously through a cloud, and that information can be checked remotely by an android application. Also, we are using Buzzer so that nearby people can be alerted. Thereby we can take timely action so that many natural resources and human beings will be saved from this threat.